Identification of miniature inverted-repeat transposable elements (MITEs) and biogenesis of their siRNAs in the Solanaceae: New functional implications for MITEs - Kuang, Hanhui; Padmanabhan, Chellappan; Li, Feng; Kamei, Ayako; Bhaskar, Pudota B.; Ouyang, Shu; Jiang, Jiming; Buell, C. Robin; Baker, Barbara (Genome Research, 2009)
Small RNAs regulate the genome by guiding transcriptional and post-transcriptional silencing machinery to specific target sequences, including genes and transposable elements (TEs). Although miniature inverted-repeat transposable elements (MITEs) are closely associated with euchromatic genes, the broader functional impact of these short TE insertions in genes is largely unknown. We identified 22 families of MITEs in the Solanaceae (MiS1–MiS22) and found abundant MiS insertions in Solanaceae genomic DNA and expressed sequence tags (EST). Several Solanaceae MITEs generate genome changes that potentially affect gene function and regulation, most notably, a MiS insertion that provides a functionally indispensable alternative exon in the tobacco mosaic virus N resistance gene. We show that MITEs generate small RNAs that are primarily 24 nt in length, as detected by Northern blot hybridization and by sequencing small RNAs of Solanum demissum, Nicotiana glutinosa, and Nicotiana benthamiana. Additionally, we show that stable RNAi lines silencing DICER-LIKE3 (DCL3) in tobacco and RNA-dependent RNA polymerase 2 (RDR2) in potato cause a reduction in 24-nt MITE siRNAs, suggesting that, as in Arabidopsis, TE-derived siRNA biogenesis is DCL3 and RDR2 dependent. We provide evidence that DICER-LIKE4 (DCL4) may also play a role in MITE siRNA generation in the Solanaceae.
10.1101/gr.078196.108